PENGARUH KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MEDIASI - Triwibowo, Wahyu; Arsanti, Tutuk Ari (Proceeding SENDI_U, 2016)
Organizational Citizenship Behavior can arise from various factors within the organization, including the existenceof high employee job satisfaction and organizational commitment. When employees have work satisfaction,employee will work optimally, even doing some things that may be beyond their duties. As well as when a personhas a high commitment to the organization, employees will do anything to advance his company. According to theprevious research, it found that there is effect of work satisfaction to OCB directly or indirectly. Organizationalcommitment is a mediator variable that has found in previous research. The purpose of this study to determinewhether the organizational commitment mediates the effect of job satisfaction on Organizational CitizenshipBehaviour (OCB). This research used a quantitative method with survey approach. The population of this researchare all employees who work at Villa Almarik Resort, 75 employees. Path analysis through Sobel test is used toanalysis the hypothesis. The results showed that the indirect effect of job satisfaction variables on OCB throughorganizational commitment can be accepted. This suggests that the effect of job satisfaction on OCB would behigher if through organizational commitment.Keywords: Job Satisfaction, Organizational Commitmentand, Organizational Citizenship Behavior